La calidad de la atención en salud, más allá de la mirada técnica y normativa (2011)
ABSTRACT: To understand the perceptions the users have about health care quality received in three health care institutions in the city of Medellin, Colombia. Methodology. Qualitative approach from the perspective of focused ethnography. Data were obtained through semi structured interviews, non participant observation, field journey and documentary revision. Informed consent from the participants and hospitals authorization was obtained. The participants were 18 users. Results. Categories resulting from the analysis were: the health care way, meeting with the other, health care differences, and how to solve the complaint. Conclusion. From the users view, there are difficulties with health care associated with health care providers, especially with the daily relationship with the users. This situation is a consequence of the efficiency and technical model, where the user as a subject and person is every time more invisible.